Importance of second and third generation ELISA test in detection of HVC antibody - Sedat BOYACIOĞLU,; Münire TURAN,; Gürden GÜR,; Mete ÖZDOĞAN,; Orhan ÖZGÜR,; Hasan TELATAR, (Turkish Journal of Gastroenterology, 2019)
-